Antibacterial and antifungal activity of extracts and exudates of the Amazonian medicinal tree Himatanthus articulatus (Vahl) Woodson (common name: Sucuba) - Sequeira, Bianca Jorge (2009)
Himatanthus articulatus (Vahl) Woodson is a tree found in the northern Amazon savannahs (common name: sucu-ba) that is used in local Amerindian medicine. Leaf, bark and branch wood methanol extracts, sequentially obtained hexane, ethyl acetate and methanol extracts and latex were evaluated for antifungal and antibacterial activities against American Type Culture Collection (ATCC) and local clinical strains using the disc diffusion method. Metha-nol extracts and latex inhibited Candida albicans, leaf methanol extracts inhibited Staphylococcus aureus and Bacil-lus subtilis and bark methanol extracts inhibited B. subtilis. Active extracts inhibited the ATCC and clinical strains. Polar antifungal and antibacterial principles in latex and extracts are thought to be responsible for the inhibition.